Fostering Undergraduate Research Change at the System and Consortium Level: Perspectives From the Council on Undergraduate Research. Issue 169 (March 2015) - Malachowski, Mitchell; Osborn, Jeffrey M.; Karukstis, Kerry K.; Ambos, Elizabeth L.; Kincaid, Shontay L.; Weiler, Daniel
Abstract : In this final chapter, we summarize the lessons learned from working with six systems/consortia to enhance and expand undergraduate research. The theory of change model for systems/consortia differs in significant ways from the change processes exhibited by individual institutions, offering important insights for academic leaders as they seek to leverage educational change effectively.